The estimate of topographical variables for soil erosion modelling through geoprocessing - De Morisson Valeriano, Márcio (2000)
: The technical requirements for geoprocessing of topographical data were studied, from digitizing until the obtention of the topographical factor of the Universal Soil Loss Equation (USLE), through calculation of slope (angle) and length. The development of the methods were based on data from manual cartographic survey and geographical information system (GIS) results of Sao Joaquim creek watershed (Pirassununga, SP, Brazil). A preliminary study, on the spatial behavior of the variables, their relations to local relief and to the topographical factor sensibility supported the selection of geoprocessing optimal procedures and parameters to achieve the maximum quality of the generated digital terrain models (DTM), and therefore, of all GIS results. Tests with the slope calculation indicated the need of high resolution, and the importance of post-processing (smoothing) and numerical fit. A method to obtain slope length was developed using spatial analysis functions of GIS. Results of the anisotropic cost analysis were correlated to measureed length, requiring linear fit. Errors for digital estimates prevailed in steep relief areas.